A competitive radioluminescence material - LiF:Mg, Cu, P for real-time dosimetry. (February 2022) - Zhang, Siyuan; Tang, Kaiyong; Fan, Haijun; Fu, Li
Abstract: Currently, common radioluminescent (RL) materials have their own advantages and disadvantages in real-time dosimetry. The most attractive RL materials are tissue equivalent materials with stable sensitivity, weak afterglow, and a wide dose-rate linear range. LiF has a low effective atomic number, and previous studies have reported the RL sensitivity of LiF:Mg, Ti is dose-dependent. LiF:Mg, Cu, P can also emit RL during irradiation, which may be used for real-time dose monitoring. The purpose of this paper is to investigate dose characteristics of RL in LiF:Mg, Cu, P based on a developed optical fiber system and a commercial TL/OSL reader (Risφ TL/OSL-DA-20C/D). The results indicated that the RL sensitivity of LiF:Mg, Cu, P is not as good as Al2 O3 :C, but comparable to LiF:Mg, Ti. It can be inferred that LiF:Mg, Cu, P is suitable for high dose rate measurements. LiF:Mg, Cu, P showed almost a constant sensitivity to absorbed dose and a weak afterglow signal, which implies the accurate dose rates can be obtained quickly without sensitivity corrections. In addition, LiF:Mg, Cu, P has a good linear dose-rate response ranging from 0.76 mGy/h to 8.02 Gy/h, similar to LiF:Mg, Ti, and a superior repeatability (∼1.36%) to LiF:Mg, Ti. In conclusion, LiF:Mg, Cu, P is a competitive RL material for real-time dosimetry with its own advantages. Highlights: The RL sensitivity of LiF:Mg, Cu, P is comparable to LiF:Mg, Ti. LiF:Mg, Cu, P showed almost a constant sensitivity to absorbed dose. The accurate dose rates can be obtained without sensitivity corrections. LiF:Mg, Cu, P has a good linear dose-rate response ranging from 0.76 mGy/h to 8.02 Gy/h. LiF:Mg, Cu, P is a competitive RL material for real-time dosimetry with its own advantages.